IMPLEMENTASI OPEN ENDED PROBLEM DALAM MATA KULIAH STATISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MAHASISWA MANAJEMEN FOOD AND BAVERAGE SEKOLAH TINGGI PARIWISATA TRIATMA JAYA - Oktaviani, Laras; Tari, Nirmala (Universitas Pendidikan Indonesia, 2017)
This classroom action research aims at improving statistical problem solving ability through the implementation of open ended problems in the students of MFB E semester VI STIPAR Triatma Jaya in the academic year 2016/2017. The design of this research is Classroom Action Research in which subject was student MFB E semester VI STIPAR Triatma Jaya consisted of 25 students. Data of problem solving ability were collected by using a problem-solving test in the form of essay test. Data of problem solving abilities were analyzed quantitatively. The results of this study show that: (1) implementation of open ended problem can improve the statistical problem solving ability of student MFB E semester VI STIPAR Triatma Jaya year lesson 2016/2017. In cycle I, the students’ average problem solving ability reached 70.28, whereas in cycle II the average value of problem solving ability was successfully increased into 80.08. These results indicate that there has been an increasing in the average score of problem-solving abilities by 9.8 from cycle I to cycle II. (2) Implementation of open ended problem can improve students' statistics learning mastery MFB E semester VI STIPAR Triatma Jaya year lesson 2016/2017. In cycle I the percentage of mastery was 68%, while in cycle II the percentage of learning mastery was successfully increased to 88%. These results indicate that there has been an increasing in percentage mastery learning by 20% from cycle I to cycle II.